Development of Interactive e-Learning Media on Environmental Pollution using Prezi - Farach, Nurul; Rahman, Taufik; Siahaan, Parsaoran (Jurnal Pendidikan MIPA, 2022)
This study aims to develop an interactive learning media application based on Prezi. The methodology used in this study is the ADDIE method with a sample of class VII students. Data collection techniques were carried out through media experts and material experts including media and material expert validation questionnaires, student observation sheets, interview sheets, pretest-posttest sheets and response questionnaires. The results showed that the application of Prezi-based learning media had a media feasibility effect of 95% with very decent criteria and 95% on Prezi-based learning outcomes, with very good criteria. Student responses resulted in an average of 87% with very interesting criteria besides the results of the N-gain analysis of 0.73 which was included in the high category. effectively used in the learning process. Keywords: e-learning, interactive learning media, Prezi. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp554-568